2001
DOI: 10.1128/aem.67.7.3269-3274.2001
|View full text |Cite
|
Sign up to set email alerts
|

Toxic-Metabolite-Producing Bacteria and Fungus in an Indoor Environment

Abstract: Toxic-metabolite-emitting microbes were isolated from the indoor environment of a building where the occupant was suffering serious building-related ill-health symptoms. Toxic substances soluble in methanol and inhibitory to spermatozoa at <10 g (dry weight) ml ؊1 were found from six bacterial isolates and one fungus. The substances from isolates of Bacillus simplex and from isolates belonging to the actinobacterial genera Streptomyces and Nocardiopsis were mitochondriotoxic. These substances dissipated the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…The elevated levels of fungal aerosol in farmhouses compared to urban homes were also shown during Finnish studies [5,11,17]. In the study by Pasanen [11], the highest total culturable fungal spore counts were recorded in old rural houses (geometric mean 1012 CFU/m 3 . Moreover, the microbial contamination of indoor air was similar in farmhouses and in other rural buildings, suggesting a spread of microorganisms from agricultural sources to indoor environments [17].…”
Section: Discussionmentioning
confidence: 85%
“…The elevated levels of fungal aerosol in farmhouses compared to urban homes were also shown during Finnish studies [5,11,17]. In the study by Pasanen [11], the highest total culturable fungal spore counts were recorded in old rural houses (geometric mean 1012 CFU/m 3 . Moreover, the microbial contamination of indoor air was similar in farmhouses and in other rural buildings, suggesting a spread of microorganisms from agricultural sources to indoor environments [17].…”
Section: Discussionmentioning
confidence: 85%
“…Many fungi pose health risks, causing not only frequent allergic diseases but also immunotoxic diseases such as sick building syndrome (Burch & Levetin, 2002). Indoor fungal spores are strongly linked to respiratory diseases (Stryjakowska-Sekulska et al, 2005) and there is considerable evidence to suggest that elevated spore counts inside buildings can prompt allergy symptoms (Peltola et al, 2001). Some of the genera isolated in this study such as Stachybotrys are widely associated with symptoms of ill health in exposed people (Salkinoja-Salonen et al, 2003) and biodeterioration of damp materials (Kasznica-Kocot et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a pumilacidin-producing B. pumilus has been implicated in a case of food poisoning (13). A study by Brophy and Knoop (9) reported experimental induction of enterocolitis in guinea pigs, while some compounds produced by B. pumilus were reportedly toxic to mice, eukaryotic cells and humans (20,21,24,32).…”
Section: Discussionmentioning
confidence: 99%